Use of Hands up Media to Improve Students' Speaking Ability in English - Maslahah, Ani Agustiyani (Journal of English Teaching and Learning Issues, 2021)
Among the success of education is due to the quality of learning. The quality of learning is good because of the use of teaching aids. Likewise, the success of listening material is also supported because of the accuracy of the use of teaching aids. Here there is the use of practical teaching aids that can improve the quality of learning English, especially speaking material. Sources of data include 30 students consisting of 15 students. Data were collected through observation and documentation. To analyze the research data used descriptive quantitative methods with percentages. The percentage results are then consulted with predetermined criteria. The results show the effectiveness of hand puppet props in learning and improving students' abilities. Students become more active and motivated by the presence of hand puppet props. Props can increase students' learning motivation, thus supporting a learning atmosphere for students. The results of the evaluation of learning activities are generally good, as seen from the aspects of material suitability, understanding, analysis and synthesis, and learning intensity.